BMI and future risk for COVID-19 infection and death across sex, age and ethnicity: Preliminary findings from UK biobank (2020)
Aims: We examined the link between BMI and risk of a positive test for SARS-CoV-2 and risk of COVID19-related death among UK Biobank participants. Methods: Among 4855 participants tested for SARS-CoV-2 in hospital, 839 were positive and of these 189 died from COVID-19. Poisson models with penalised thin plate splines were run relating exposures of interest to test positivity and case-fatality, adjusting for confounding factors. Results: BMI was associated strongly with positive test, and risk of death related to COVID-19. The gradient of risk in relation to BMI was steeper in those under 70, compared with those aged 70 years or older for COVID-19 related death (Pinteraction ¼ 0.03). BMI was more strongly related to test positivity (Pinteraction ¼ 0.010) and death (Pinteraction ¼ 0.002) in non-whites (predominantly South Asians and AfroCaribbeans), compared with whites. Conclusions: These data add support for adiposity being more strongly linked to COVID-19-related deaths in younger people and non-white ethnicities. If future studies confirm causality, lifestyle interventions to improve adiposity status may be important to reduce the risk of COVID-19 in all, but perhaps particularly, non-white communities